2019
DOI: 10.1371/journal.pone.0217569
|View full text |Cite
|
Sign up to set email alerts
|

Podocin and uPAR are good biomarkers in cases of Focal and segmental glomerulosclerosis in pediatric renal biopsies

Abstract: There are controversies whether Minimal Change Disease (MCD) and Focal and Segmental Glomerulosclerosis (FSGS) are distinct glomerular lesions or different manifestations within the same spectrum of diseases. The uPAR (urokinase-type plasminogen activator receptor) and some slit diaphragm proteins may be altered in FSGS glomeruli and may function as biomarkers of the disease in renal biopsies. Thus, this study aims to evaluate the diagnostic potential of uPAR and glomerular proteins for differentiation between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…Previous results from our group have shown that podocytes have increased expression of urokinase plasminogen activator receptor (uPAR) in situ in biopsies from adult [ 8 ] and pediatric [ 9 ] patients with morphological lesions compatible with FSGS. From these findings, we evaluated the possible causes of cellular injury in podocytopathies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous results from our group have shown that podocytes have increased expression of urokinase plasminogen activator receptor (uPAR) in situ in biopsies from adult [ 8 ] and pediatric [ 9 ] patients with morphological lesions compatible with FSGS. From these findings, we evaluated the possible causes of cellular injury in podocytopathies.…”
Section: Resultsmentioning
confidence: 99%
“…Animal model studies have demonstrated the relationship between reduction in WT1-labeled podocytes and glomerulosclerosis [ 15 ]. However, we have previously shown that there is no difference in the density of WT1-labeled podocytes in biopsies of pediatric patients with FSGS and MCD [ 9 ]. Unlike other studies, we excluded glomeruli that presented sclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, plasma suPAR levels have also been found to be elevated in several extrarenal pathologies that can potentially be concomitant to FSGS, such as cancer or inflammatory disorders, among others [ 91–95 ]. Recent studies suggest that both urinary levels of suPAR [ 96 , 97 ] and uPAR detection in kidney biopsies [ 98 ] may be useful in the diagnosis of primary FSGS, but further investigation is needed. Anti-CD40 blood levels have also been associated with FSGS, with 78% accuracy to predict post-transplant FSGS recurrence [ 99 ]; however, further studies are required to confirm these results.…”
Section: Introductionmentioning
confidence: 99%